A Bibliometric Perspective on the Relationship between Periodontal Disease and Gestational Diabetes - Mayta-Tovalino, Frank; Barja-Ore, John; Liñán-Bermúdez, Alexandra; Rojas, Mirian Solis; Guevara, Zaida Zagaceta (The journal of contemporary dental practice, 2023)
To analyze the bibliometric indicators of the world scientific production on periodontal disease and gestational diabetes. Bibliometric study in which a search strategy was designed with logical operators and MESH terms. After the search and application of selection criteria, 83 articles were included. SciVal, VOSviewer, and the Bibliometrix module of R Studio were used to analyze the metadata. From 2012 to 2021, there is evidence of an increase in scientific dissemination on gestational diabetes and periodontal disease, especially in high-impact journals (79.2%). SUNY Buffalo (6), United State University, and Ege University, Turkey (5) are the most productive; however, the one that received more citations than the global average was the University of Birmingham (FWCI: 5.59). In addition, the United States, Brazil, and India were the most influential countries; while, Graziani F, Akcali A, and Buduneli N, were the most representative authors. The Journal of Periodontology and the Journal of Clinical Periodontology published the most articles, with 13 and 6, respectively. The scientific production on periodontal disease and gestational diabetes is higher in recent years, with a better proportion of articles in high-impact journals. In addition, the United States concentrates many publications, and the activity of Chilean institutions stands out. The clinical significance of this study lies in its capacity to synthesize the currently available published information regarding the correlation between periodontal disease and gestational diabetes. This study enables researchers and clinicians to ascertain the current level of knowledge on this subject.